"The post-pulmonary syndrome - results of echocardiographic driven follow up after acute pulmonary embolism". Issue 186 (February 2020) - Dzikowska-Diduch, Olga; Kostrubiec, Maciej; Kurnicka, Katarzyna; Lichodziejewska, Barbara; Pacho, Szymon; Miroszewska, Agnieszka; Bródka, Katarzyna; Skowrońska, Marta; Łabyk, Andrzej; Roik, Marek; Gołębiowski, Marek; Pruszczyk, Piotr
Abstract: Introduction: The concept of post Pulmonary Embolism syndrome includes various combinations of functional, haemodynamic or imaging abnormalities in patients after pulmonary embolism (PE). Although residual obstruction of pulmonary vascular bed is suggested to be a major cause of post Pulmonary Embolism syndrome (post-PE syndrome) other cardiopulmonary abnormalities can be responsible for functional impairment. Therefore, we analyzed the frequency of post-PE syndrome and its potential causes. Material and methods: We report data of consecutive 845 PE survivors (468 F, aged 62 ± 18 yrs) who were anticoagulated, and followed for at least 6 months. All symptomatic subjects at follow up underwent diagnostic workup. Results: 35% (290/845) of PE survivors recovered functionally, while 65% patients reported a decreased exercise tolerance compatible with post-PE syndrome. One hundred and five symptomatic cases were lost to follow up. After diagnostic workup, chronic thromboembolic pulmonary hypertension (CTEPH) was diagnosed in 38 of 450 (8.4%) symptomatic subjects and chronic thromboembolic pulmonary disease (CTED) was diagnosed in 15/450 (3.3%) of them. Chronic heart failure with reduced ejection fraction (EF) was found in 6.9% (31/450) of patients and 154 patients (34.2%) had leftsided diastolic dysfunction. Valve heart disease was detected in 6.2% (28/450), atrial fibrillation in 31/450 (6.9%), Other causes of reduced exercise tolerance include coronary artery disease in 31/450 (6.9%), pulmonary disease 42/450 (9.3%), morbid obesity 15/450 (3.3%), neoplasms 15/450 (3.3%), psychiatric disorders 1%, rheumatoid disease 1%, anemia 1%. Conclusions: Approximately 65% of PE survivors report functional impairment, despite at least 6 months of anticoagulation. Persistent pulmonary artery thromboemboli resulting in CTEPH or CTED were detected in 7.2% of PE survivors and 11.8% of symptomatic patients. Leftsided diastolic dysfunction was the most prevalent echocardiographic abnormality, and remained the most common cause of functional limitation affected 34.2% of symptomatic cases. Highlights: Functional limitation affects 65% of pulmonary embolism (PE) survivors, despite at least 6 months of anticoagulation. Leftsided diastolic dysfunction remains the most common cause of functional limitation. CTEPH or CTED were detected in 7.2% of all PE survivors and 11.8% of patients with functional limitation.